ANALISIS KOMPARATIF PREDIKSI KEBANGKRUTAN DENGAN METODE ALTMAN Z-SCORE DAN ZMIJEWSKI X-SCORE - Hafizah, Dita; Sa'adah, Lailatus (Universitas Prof. Dr. Hazairin SH, 2024)
The purpose of this study is to determine if there is a difference between the Altman and Zmijewski methods in predicting bankruptcy. This type of research is comparative with quantitative methods. The sample used is transportation subsector companies listed on the Indonesia Stock Exchange for the 2019-2023 period, totaling 7 issuers, using purposive sampling technique. This study uses the independent sample t-test comparative test. The results of the research in the Independent Sample T-Test test are a t value of -2.686 with a probability of 0.010. This means that there are differences between Altman and Zmijewski methods in predicting bankruptcy. The Altman method is superior in predicting bankruptcy with an accuracy rate of 74.29%, while the Zmijewski method obtained an accuracy value of 37.14%. This means that the Altman method is more accurate and reliable in predicting corporate bankruptcy compared to the Zmijewski method.